Optical and structural properties of rice husk silicate incorporated borotellurite glasses doped with erbium oxide nanoparticles - Muhammad Noorazlan Abd Azis (Tanjong Malim, 2019)
Optical and structural properties of rice husk silicate incorporated borotellurite glasses doped with erbium oxide nanoparticles by Muhammad Noorazlan Abd Azis